Penerapan Algoritma VLBE Pada Aplikasi Kompresi File - Binaria Tarigan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Data or files have a very important role for every person who uses computers every day. Sending data or files over a network or media is just another large size, so it takes a long time also requires a large storage space in the process. File submission also requires certainty so that the file sent cannot be stolen or changed by an irresponsible person, so we need a way to overcome these problems. Compression technique is one technique to reduce the large capacity of a file that is used by the file provider in order to secure a file. The process of compressing and supplying PDF files is done by using compressing the data first with the Variable Length Binary Encoding algorithm, then the application designed will carry out these processes so that it will produce compressed and encoded files.